STUDENT PERCEPTIONS OF THE USE OF LEARNING VIDEOS AS LEARNING MEDIA IN CLASS TO INCREASE STUDENT LEARNING MOTIVATION - Rezikna; Herawati; Herlina (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to determine students' perceptions of the use of instructional videos in classroom learning as alternative media for students at SD Negeri 1 Tatura Palu. The subjects of this research were 22 students in class 3B of SD Negeri 1 Tatura Palu. This type of research is a qualitative research method that describes the results of using learning videos. The instrument used to collect data was a questionnaire. The results of data analysis show that the use of learning videos in classroom learning provides positive perceptions for students. These results are also reinforced by students' perceptions that learning videos are very positive in class because they can increase students' learning motivation. Most students answered that learning videos motivated them to learn. The results of this research can be concluded that learning videos have a positive effect in increasing students' interest in learning.